ROLE OF PANCHAKARMA IN RESTLESS LEG SYNDROME - A CASE STUDY (AYUSHDHARA, 2020)
Restless leg syndrome (RLS) is common medical condition, which is characterized by unpleasant leg sensation that is eased by movement (Motor restlessness). It has a strong familial tendency and can present with day time somnolence due to poor sleep. A need to move the legs usually accompanied or caused by uncomfortable, unpleasant sensation in legs, which worsens during period of rest or being inactivity such as lying or sitting. It generally worsens only during evening or night and relieves partially by movement such as walking or stretching, which are the diagnostic criteria of RLS. As it is a syndrome, it cannot be co-related to a single disease in Ayurveda. In RLS both Sensory and Motor changes takes place which is governed by Vatadosha, where sensation can be considered as Sensory thing (Gandana) and Movement is a Motor thing (Gati) which comes in responses to Sensory thing. When there is imbalance between the same, it can causes disturbances related both Sensory and Motor responses. Vrudha Vayu due to Nidana causes different types of Shula. Pain that aggravates during nights and Sheetha kala shows its predominancy. Pindikodweshtana appreciated in the case can also be considered under Nanatmaja Vatavyadhi. Thus by considering all these, it can be included under the broad heading of Vata vyadhi. Amapachana followed by Samanya Vatavyadhi Chikitsa in the form of Rukshana karma followed Snehana and Swedana were the treatment modalities adopted in the case, which showed significant improvements in all the symptoms patients had.